2016
DOI: 10.1038/srep34484
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone recognition and characterization of three pheromone-binding proteins in the legume pod borer, Maruca vitrata Fabricius (Lepidoptera: Crambidae)

Abstract: Pheromone-binding proteins (PBPs) are essential for the filtering, binding and transporting of sex pheromones across sensillum lymph to membrane-associated pheromone receptors of moths. In this study, three novel PBP genes were expressed in Escherichia coli to examine their involvement in the sex pheromone perception of Maruca vitrata. Fluorescence binding experiments indicated that MvitPBP1-3 had strong binding affinities with four sex pheromones. Moreover, molecular docking results demonstrated that six amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…Although structural modeling was used to predict the "presumed" structures of MvitPBPs (Mao et al, 2016), future studies should confirm their three-dimensional structures by X-ray diffraction and/or NMR spectroscopy. conserved in lepidopteran PBPs (Sandler et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although structural modeling was used to predict the "presumed" structures of MvitPBPs (Mao et al, 2016), future studies should confirm their three-dimensional structures by X-ray diffraction and/or NMR spectroscopy. conserved in lepidopteran PBPs (Sandler et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Malini, Schafleitner, Muthukalingan, & Srinivasan, 2013), where we reported the phylogeny of M. vitrata based on MvitPBP sequences. Subsequently, the role of PBPs in sex pheromone perception in M. vitrata was studied in China(Mao et al, 2016), but PBPs were never used in population genetics of this organism. Since geographically distinct Maruca populations were identified using coxI(Malini et al, 2015) and ITS2(Malini, Schafleitner, Srinivasan, & Krishnan, 2014), the differences in the protein coding sequences ofMaruca PBPs from Asia, Africa, Oceania, and South America were characterized in this study.…”
mentioning
confidence: 99%
“…The mRNA expression profiles of PBPs and GOBPs revealed that all of them are more significantly expressed (at least six‐fold) in male antennae than that in female antennae. Surprisingly, there was little trace expression in wings, legs, etc., and this expression pattern was similar with the results reported in Bombyx mori , Helicoverpa armigera , Maruca vitrata and Spodoptera exigua . GOBP1 and PBP2 were especially higher in males (200–400 times), and this male‐biased expression suggested that they may play vital roles in the perception of female sex pheromones.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, there was little trace expression in wings, legs, etc., and this expression pattern was similar with the results reported in Bombyx mori, Helicoverpa armigera, Maruca vitrata and Spodoptera exigua. [43][44][45][46][47] GOBP1 and PBP2 were especially higher in males (200-400 times), and this male-biased expression suggested that they may play vital roles in the perception of female sex pheromones. Furthermore, the expression pattern in female and other male tissues probably suggested that they were not specific to antennae or involved in the monitoring of the pheromones or responding to stimuli.…”
Section: Wileyonlinelibrarycom/journal/psmentioning
confidence: 99%
“…Perception of odorants and sensitive chemosensory systems are essential for developmental, physiological, and functional behaviors of insects, such as mating, partner identification through chemical signals, host location, and interspecific communications (Mao et al ., ). Insects can detect and discriminate semiochemicals through numerous receptors and olfactory proteins, including chemosensory proteins (CSPs), odorant binding proteins (OBPs), odorant receptors (ORs), sensory neuron membrane proteins (SNMPs), and odorant degrading enzymes (ODEs) (Pelosi et al ., ; Zhang Q. H. et al ., ).…”
Section: Introductionmentioning
confidence: 97%